2001
DOI: 10.1002/1528-0691(2001)1:1<24::aid-tcr5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

TheClostridium cellulovorans cellulosome: An enzyme complex with plant cell wall degrading activity

Abstract: Cellulose comprises a major portion of biomass on the earth, and the turnover of this material contributes to the CO2 cycle. Cellulases, which play a major role in the turnover of cellulosic materials, have been found either as free enzymes that work synergistically, or as an enzyme complex called the cellulosome. This review summarizes some of the general properties of cellulosomes, and more specifically, the properties of the Clostridium cellulovorans cellulosome. The C cellulovorans cellulosome is an extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This is similar to the secretion of hemicellulase, for example aerobic fungi Trichoderma reesei and Aspergillus niger secrete 8 and 12 hemicellulases in high concentrations, respectively [85]. Fungi, such as T. reesei and A. niger , produce large amounts of extracellular cellulolytic enzymes, whereas some strains, including bacteria mainly from the class Clostridia, such as Clostridium cellulovorans [86-88] and Clostridium thermocellum [89,90], a few anaerobic fungi [91,92], and Eisenia fetida [93], mostly produce cellulolytic enzymes in a multienzyme complex called cellulosome, which is associated with the degrading cell wall [94,95]. …”
Section: Secretory Pathways In Different Organismsmentioning
confidence: 99%
“…This is similar to the secretion of hemicellulase, for example aerobic fungi Trichoderma reesei and Aspergillus niger secrete 8 and 12 hemicellulases in high concentrations, respectively [85]. Fungi, such as T. reesei and A. niger , produce large amounts of extracellular cellulolytic enzymes, whereas some strains, including bacteria mainly from the class Clostridia, such as Clostridium cellulovorans [86-88] and Clostridium thermocellum [89,90], a few anaerobic fungi [91,92], and Eisenia fetida [93], mostly produce cellulolytic enzymes in a multienzyme complex called cellulosome, which is associated with the degrading cell wall [94,95]. …”
Section: Secretory Pathways In Different Organismsmentioning
confidence: 99%
“…We sequenced the entire genome of Clostridium cellulovorans (Tamaru et al [2010a]) and identified all genes, including those that encode proteins of known and unknown functions, related to cellulosome composition (Tamaru et al [2010a]). Genome analysis of C. cellulovorans indicated the presence of 57 cellulosomal enzymes-encoding genes including 4 scaffold proteins-encoding genes and 53 cellulosomal enzymes-encoding genes with dockerin domains (Doi and Tamaru [2001]). The major scaffold protein, CbpA, is comprised of 9 cohesin domains that bind to various cellulosomal enzymes via cohesin-dockerin interactions.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) The efficiency of the synergistic or combined action of hemicellulases has been reported to be higher than that of their individual actions. 5) Some cellulolytic bacteria and filamentous fungi produce a set of cellulases and hemicellulases which synergistically hydrolyze crystalline celluloses and hemicelluloses to smaller oligosaccharides and subsequently to monomeric sugars upon the cleavage action of exo-enzymes.…”
mentioning
confidence: 99%